SPECIFIC ASPECTS OF THE DEVELOPMENT OF ENTERPRISES BASED ON CIVIL SOCIAL RIGHTS - Jovli Narzullaevich, Tursunov (Journal of Learning on History and Social Sciences, 2025)
Objective: This study examines the legal aspects influencing enterprise development under Uzbekistan’s civil law framework, with a focus on business registration, contractual obligations, and liability. It addresses the challenges entrepreneurs face in complying with civil regulations and explores the broader implications for economic stability. Method: The research employs a qualitative legal analysis, reviewing constitutional provisiosns, civil codes, and regulatory frameworks governing entrepreneurship. Case studies and judicial precedents are analyzed to assess the practical application of these laws. Results: Findings reveal that legal capacity, property rights, and contractual obligations significantly impact entrepreneurial activities. The regulatory framework provides mechanisms for legal recourse through commercial courts, ensuring business protection while addressing monopolistic practices. However, challenges such as bureaucratic inefficiencies in business registration and contract enforcement remain prevalent. Novelty: Unlike previous studies, this research highlights the intersection of legal capacity and entrepreneurship, demonstrating how civil law principles shape business operations. By bridging the gap between legal theory and entrepreneurial practice, this study provides insights for policymakers to refine business regulations, enhance legal literacy, and foster a more efficient business environment.